HUBUNGAN PENGETAHUAN DAN KEAKTIFAN IBU MENGIKUTI KELAS IBU BALITA TERHADAP STATUS GIZI BALITA DI DESA PANIPAHAN DARAT WILAYAH KERJA PUSKESMAS PANIPAHAN KABUPATEN ROKAN HILIR - Siti Mauliza; Rifa Yanti; Lisviarose Lisviarose; Meirita Herawati (Ensiklopedia of Journal, 2026)
Nutritional status problem of toddlers, which remains a health issue in Panipahan Darat Village, Panipahan Health Center Working Area, Rokan Hilir Regency. The study aimed to analyze the relationship between mothers’ knowledge and their activeness in attending toddler classes with toddlers’ nutritional status. This research used an analytical design with a cross-sectional approach. It was conducted in June–August 2024 in Panipahan Darat Village. The population consisted of all mothers with toddlers, with a sample of 84 respondents selected using proportional random sampling. Inclusion criteria included mothers with children aged 6–59 months, residing in the study area, and willing to participate. Data were collected using questionnaires and observations, processed through editing, coding, entry, and cleaning, and analyzed using chi-square tests. The results showed a significant relationship between mothers’ knowledge (p=0.015) and activeness in attending toddler classes (p=0.008) with toddlers’ nutritional status. The study concluded that improving mothers’ knowledge and participation in toddler classes contributes positively to enhancing children’s nutritional status. The health center is advised to strengthen nutrition education programs and increase mothers’ participation in such classes. Keywords: Knowledge, Mother’s Activeness, Toddler Classes, Nutritional Status